Modificación de la vía aérea superior en las osteotomías mandibulares - Argandoña-P., Juan; Mercier, Jacques; Naranjo, Rodrigo Felipe (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The sagital diameter of the phart airrlay has been studied in the pre and past-opera til'e radiographs in twenty patients with dentofacial deformities, whom were submitted to corrective mandibular asteetamies for advancement or set back. Results shell's that the pharrm,real airival. Was modified in both procedures, increasing its sagital diameter in mandibular advancen7ent asteetomies and decreasing in set back mandibular osteotomies. We concluded that the pharyngeal dint-d1; T1 th his respiratory related factors will be modified with mandibular movements and the surgeon must be in knowledge of this aspects to decide the adequate orthognatic surgical procedure.